DLC-treated aramid-fibre composites: Tailoring nanoscale-coating for macroscale performance. (8th February 2019) - Kanerva, M.; Korkiakoski, S.; Lahtonen, K.; Jokinen, J.; Sarlin, E.; Palola, S.; Iyer, A.; Laurikainen, P.; Liu, X.W.; Raappana, M.; Tervakangas, S.; Valden, M.
Abstract: This work aims to quantify the effect of a diamond-like carbon coating (DLC) treatment of aramid fibres and to reveal the conversion of a fibre-level performance leap on the macroscale mechanical behaviour. The DLC-based coating is applied directly to the reinforcement and laminates are infused with an epoxy matrix. After characterisation of the coated surfaces, the performance of the composite is analysed via interlaminar shear testing, fatigue testing and damage tolerance testing, microbond tests, and 3D finite element simulation using a cohesive zone model of the interface. The results show that the coating treatment improves the fatigue life and the S-N curve slope for the laminates, while the residual strength after impact damage and environmental conditioning (water immersion at 60 °C) remains high. The scaling factor to convert the performance on macroscale was determined to be 0.17–0.39 for the DLC-based fibre treatment.